Institutional roots of economic decline: lessons from Italy. (14th November 2020) - Simoni, Marco
Abstract: The economic decline of Italy between the mid-1990s and the outset of the financial crisis is a critical case in European political economy because its model of capitalism was deeply reformed at the time when its decline commenced. This paper argues that the Italian economic stagnation cannot be attributed to the lack of market-friendly reforms in a globalized economic context, as argued by previous literature. Instead, Italian economic decline is a consequence of institutional change which on the one hand has destroyed previous institutional complementarities, and on the other hand has led to an incoherent, or 'hybrid, ' capitalist setting. Under the lenses of the Varieties of Capitalism approach, this paper reviews the main reforms in the fields of corporate governance and finance as well as in the labor market. It shows that such reforms established new institutions alternatively apt to support both strategic coordination and market coordination, resulting in institutional incoherence, and mixed incentives. In the short-run, incoherent reforms have reduced the availability of capital to SMEs; in the longer-run, they failed to give actors incentives to pursue innovation. This paper contributes theories of economic growth/decline focused on the supply-side of the economy and it is compatible with other – non-rival – explanations focused on the demand-side.